2011
DOI: 10.1261/rna.2475211
|View full text |Cite
|
Sign up to set email alerts
|

Identification of compounds that decrease the fidelity of start codon recognition by the eukaryotic translational machinery

Abstract: Translation initiation in eukaryotes involves more than a dozen protein factors. Alterations in six factors have been found to reduce the fidelity of start codon recognition by the ribosomal preinitiation complex in yeast, a phenotype referred to as Sui _ .No small molecules are known that affect the fidelity of start codon recognition. Such compounds would be useful tools for probing the molecular mechanics of translation initiation and its regulation. To find compounds with this effect, we set up a high-thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
4
27
0
1
Order By: Relevance
“…Thus, SUI5 might stabilize the closed complex only in response to the UUGanticodon mismatch and be unable to compensate for the destabilizing effect of poor context. The SUI3-2 mutation in eIF2␤, by contrast, increases initiation from nearly all functional near-cognate triplets in vivo (21,46) in addition to its ability (shown here) to overcome poor context at SUI1.…”
Section: Metmentioning
confidence: 66%
“…Thus, SUI5 might stabilize the closed complex only in response to the UUGanticodon mismatch and be unable to compensate for the destabilizing effect of poor context. The SUI3-2 mutation in eIF2␤, by contrast, increases initiation from nearly all functional near-cognate triplets in vivo (21,46) in addition to its ability (shown here) to overcome poor context at SUI1.…”
Section: Metmentioning
confidence: 66%
“…If fidelity is impaired, combining L-Leucine with a drug that corrects fidelity defects may be required. Indeed, drugs targeting ribosomal fidelity are an active field of research: drug screens have identified compounds that decrease the fidelity of start codon initiation (170). Moreover, ataluren (Translarna), a drug promoting premature stop-codon read-through (171), has received market authorization from the European Commission and is in clinical trials for treatment of diseases caused by nonsense mutations such as Duchenne muscular dystrophy and cystic fibrosis (172,173).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…We asked whether they also differ in their effects on utilization of different near-cognates by comparing expression of firefly luciferase reporters harboring different start codons normalized for expression of a renilla luciferase reporter bearing an AUG codon (Takacs et al 2011). Interestingly, the G31A:C39U ASL substitution elevates utilization of UUG, CUG, or GUG triplets, all first-base mismatches, but not AUA or ACG near-cognates with second-or third-base mismatches; whereas this bias does not exist for the G70A substitution in the acceptor stem (Supplemental Fig.…”
Section: G31:c39 Discriminates Preferentially Against Near-cognates Wmentioning
confidence: 99%